2022
DOI: 10.1111/1471-0528.17124
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity among undocumented migrant women in the PreCARE prospective cohort study

Abstract: Objective: To assess the risk of severe maternal outcomes among migrant women, considering both their legal status and birthplace; in Europe, migrant women, especially from sub-Saharan Africa, have higher risks of adverse maternal outcomes compared with non-migrants and legal status, a component of migrant condition, may be an important, and potentially actionable, risk factor. Design: Prospective cohort study.Setting: Four maternity units around Paris in 2010-12.Sample: A total of 9599 women with singleton pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Eslier et al ( 21 ) found that undocumented migrants in France had a higher risk of severe maternal morbidity (33/715 [4.6%] vs. 129/4523 [2.9%]; absolute difference 1.7%, 95% CI 0.4%–3.6%; a OR 1.68, 95% CI 1.12–2.53), when compared to the reference group, it was discovered that undocumented migrants had hypertensive problems at least twice as prevalent as non-migrants or legal migrants. However, this study indicated that only undocumented migrants born in sub-Saharan Africa were at a significantly increased risk when considering both their location of birth and their legal status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eslier et al ( 21 ) found that undocumented migrants in France had a higher risk of severe maternal morbidity (33/715 [4.6%] vs. 129/4523 [2.9%]; absolute difference 1.7%, 95% CI 0.4%–3.6%; a OR 1.68, 95% CI 1.12–2.53), when compared to the reference group, it was discovered that undocumented migrants had hypertensive problems at least twice as prevalent as non-migrants or legal migrants. However, this study indicated that only undocumented migrants born in sub-Saharan Africa were at a significantly increased risk when considering both their location of birth and their legal status.…”
Section: Resultsmentioning
confidence: 99%
“…These factors such as language and cultural differences, socio-economic conditions, and fear of deportation also double as some of the barriers to accessing ANC. Eslier et al ( 21 ) hypothesised that prenatal care utilisation was inadequate for UMs, both in terms of quantity and quality, and suggested that socioeconomic and language barriers may be to blame for this group of women's underutilisation of ANC services in comparison to non-migrants and other categories of migrants. In spite of the fact that ANC is essential for the detection, monitoring, and treatment of several pregnancy-related health problems, UMs still find it difficult to access their legal rights, making it difficult for them to access and receive care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous systematic reviews, we have included all data available from high-income countries and not only those in Europe [8,35]. This offers the opportunity to compare national contexts with various migration demographic patterns, as well as various [31] and 2022 [64]; Wahlberg et al 2013 [72]; Zwart et al 2008 [9], 2010 [65] and 2011 [66]; Van Hanegem et al 2011 [67]; Urquia et al 2015 [40] and 2017 [15]. CI, confidence interval; df, degrees of freedom; IV, inverse variance; RR, risk ratio.…”
Section: Plos Medicinementioning
confidence: 99%
“…Although the performance of this screening has not been evaluated in pregnant women, the French Health Authority has recommended since 2007 Pap tests for all woman at the beginning of pregnancy if their last test took place more than three years earlier [ 30 ]. Maternal health inequalities according to maternal place of birth have been described in high-income countries, specifically in France [ 31 , 32 ]. It is important to know if these inequalities also affect cervical cancer screening during pregnancy.…”
Section: Introductionmentioning
confidence: 99%